Results of various somatic mutations detection in patients with chronic myeloid leukemia - E. A. Kuzmina; E. Yu. Chelysheva; B. V. Biderman; O. A. Shukhov; E. A. Stepanova; E. P. Gadzhieva; A. N. Petrova; I. S. Nemchenko; A. V. Bykova; M. A. Guryanova; A. V. Kokhno; A. G. Turkina; et al. (Онкогематология)
Background. Somatic mutations in chronic myeloid leukemia (CML) patients are considered as possible factors for the failure of tyrosine kinase inhibitor (TKI) therapy, and the study of their characteristics is of interest.Aim. To evaluate the genetic profile of blood cells in CML patients using nextgeneration sequencing.Materials and methods. Retrospective study was conducted in two groups of patients: group 1 with TKI therapy failure (n = 29) and group 2 with optimal response to TKI therapy (n = 29). The target panel for nextgeneration sequencing included 19 genes: ASXL1, DNMT3A, FLT3, IDH1, IDH2, NPM1, RUNX1, SF3B1, SRSF2, TET2, TP53, U2AF2, KIT, WT1, CEBPA, ZRSR2, JAK2, GATA2, ABL1. In order to assess clonal evolution, additional samples were examined at a retrospective point in time closest to the primary CML diagnosis.Results. In group 1, mutations in 8 genes (including ABL1) were identified in 19/29 (66 %) patients. Excluding ABL1, mutations were identified in 15 (52 %) patients. In 9 (31 %) patients, >1 mutation (2 to 4) was detected. Frequency of genes mutations in group 1: ABL1 in 11 (38 %) patients, ASXL1 in 9 (31 %) patients, DNMT3A in 3 (10 %) patients, RUNX1, CEBPA in 2 patients (7 %), WT1, NPM1, TET2 in 1 patient (3.5 %). In 7 (24 %) patients there was a combination of mutations in ABL1 gene and in another gene; the most frequent combination of mutations in genes: ABL1 + ASXL1 – in 4 patients (14 %). The dynamics of mutant clones in group 1 was evaluated in 21/29 (72 %) patients. In 10/21 (48 %) patients somatic mutations in genes appeared during CML treatment, in 14/21 (67 %) patients previously detected mutations persisted, in 1 (5 %) the mutation disappeared. In group 2, somatic mutations were detected in 2/29 (7 %) patients: in DNMT3A (ariant Allele Frequency (AF) 5 %) and TP53 (AF 9 %) genes – these mutations were not detected at the diagnosis of CML. In one patient ASXL1 mutation (AF 5 %) was detected only at diagnosis, and was not detected subsequently with optimal response to therapy.Conclusion. The presence of somatic gene mutations is associated with a resistant CML course: somatic mutations in genes other than ABL1 were more common in CML patients with TKI therapy failure than in those with optimal response: 52 % vs. 7 % (p ≤0.05). Mutations in ASXL1 (31 %) and DNMT3A (10 %) were the most frequently detected. The frequency of ABL1 and ASXL1 mutations combination amounted to 14 %. uring followup, somatic mutations predominantly persisted or appeared over time in CML patients with TKI therapy resistance.